1998
DOI: 10.1021/jp9802836
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Laser-Ablated Co and Ni Atoms with Nitrogen Atoms and Molecules. Infrared Spectra and DFT Calculations of Metal Nitride Molecular Species and Complexes

Abstract: Laser-ablated Co and Ni atoms, co-deposited with pure nitrogen at 10 K, gave a strong new 795.3 cm -1 band with cobalt and a 838.8, 836.1 cm -1 isotopic doublet (2.5/1.0) with nickel, which exhibited 14/15 isotopic ratios appropriate for the diatomic CoN and NiN molecules. In solid argon, CoN absorbs at 826.5 cm -1 and gives way on annealing to bands at 795.8 and 792.0 cm -1 , which are due to (NN) x CoN complexes. Density functional theory (DFT) calculations predict quintet and quartet ground states for CoN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
79
2
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(98 citation statements)
references
References 26 publications
16
79
2
1
Order By: Relevance
“…It seems BH-LYP gives a bond distance comparable to the MRCI study, and the dissociation energy is also close (1.10 eV at our BHLYP calculation, 1.36 eV at MRCI 21 ). However, BHLYP predicts a much lower vibrational frequency (516 cm Ϫ1 ) compared both the experiment (832.4 cm Ϫ1 ) 15 and previous DFT calculation [841(18) cm Ϫ1 ], 14 and extremely small IP (0.07) is obtained compared with the other four methods (Table 3). This indicates that further study in both experiment and advanced theory is necessary for NiN.…”
Section: Ninmentioning
confidence: 60%
See 2 more Smart Citations
“…It seems BH-LYP gives a bond distance comparable to the MRCI study, and the dissociation energy is also close (1.10 eV at our BHLYP calculation, 1.36 eV at MRCI 21 ). However, BHLYP predicts a much lower vibrational frequency (516 cm Ϫ1 ) compared both the experiment (832.4 cm Ϫ1 ) 15 and previous DFT calculation [841(18) cm Ϫ1 ], 14 and extremely small IP (0.07) is obtained compared with the other four methods (Table 3). This indicates that further study in both experiment and advanced theory is necessary for NiN.…”
Section: Ninmentioning
confidence: 60%
“…Except at BHLYP (1.797 Å), our calculated bond distances are close to the results of MRSDCIϩQ (1.622 Å), 26 slightly longer than previous DFT (by use of Vosko-Wilk-Husair potential) value (1.588 Å). 14 The pure exchange functional methods BLYP (834 cm…”
Section: Mnnmentioning
confidence: 99%
See 1 more Smart Citation
“…[120] Later studies showed, however, that this assignment is incorrect, and that the complex is more likely to be linear (that is, with end-on coordination of the N 2 ligand). [121] DFT + has been studied in the gas phase by ion cyclotron resonance mass spectrometry. [122] A ligand-substitution reaction (displacement of N 2 by CH 4 ) was used to…”
Section: Groupmentioning
confidence: 99%
“…No theoretical literature could be found on CoP or RhP. However, DFT calculations on the lowest singlet, triplet, and quintet states of CoN have been reported by Andrews et al [36], giving 5 D as the ground state. …”
Section: Theoretical Resultsmentioning
confidence: 99%